2014
DOI: 10.1007/s10964-014-0183-y
|View full text |Cite
|
Sign up to set email alerts
|

Involving Youth in Program Decision-Making: How Common and What Might it Do for Youth?

Abstract: The strategy of sharing program decision-making with youth in youth programs, a specific form of youth-adult partnership, is widely recommended in practitioner literature; however, empirical study is relatively limited. We investigated the prevalence and correlates of youth program decision-making practices (e.g., asking youth to help decide what activities are offered), using single-level and multilevel methods with a cross-sectional dataset of 979 youth attending 63 multipurpose after-school programs (averag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
50
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 61 publications
(52 citation statements)
references
References 27 publications
1
50
0
1
Order By: Relevance
“…Youth's involvement has been measured quantitatively, through youth report (e.g., Ramey et al, 2017). Quantitative dimensions typically include youth voice or, similarly, youth input or ownership , as well as collaborative relationships with adults (e.g., Akiva et al, 2014). At times, researchers have separately described youth's program engagement as a third dimension, involving youth's perceptions of the work as valuable and of themselves as active participants (Ramey et al, 2017).…”
Section: Settings Measurement and Rates Of Youth-adult Partnershipmentioning
confidence: 99%
See 4 more Smart Citations
“…Youth's involvement has been measured quantitatively, through youth report (e.g., Ramey et al, 2017). Quantitative dimensions typically include youth voice or, similarly, youth input or ownership , as well as collaborative relationships with adults (e.g., Akiva et al, 2014). At times, researchers have separately described youth's program engagement as a third dimension, involving youth's perceptions of the work as valuable and of themselves as active participants (Ramey et al, 2017).…”
Section: Settings Measurement and Rates Of Youth-adult Partnershipmentioning
confidence: 99%
“…At times, researchers have separately described youth's program engagement as a third dimension, involving youth's perceptions of the work as valuable and of themselves as active participants (Ramey et al, 2017). Youth involvement in youth-adult partnerships also has been measured quantitatively through adult report although and at least one study has indicated that youth and adult reports of youth voice 42 in program decisions were relatively well aligned (Akiva et al, 2014). Qualitative studies of youth involvement have similarly entailed interviews with youth and adults to uncover youth voice and engagement in the target program (e.g., Akiva & Petrokubi, 2016;Dawes & Larson, 2011).…”
Section: Settings Measurement and Rates Of Youth-adult Partnershipmentioning
confidence: 99%
See 3 more Smart Citations